Asuhan Keperawatan Gerontik Hambatan Mobilitas Fisik Pada TN. S Dengan Stroke Non Hemorogik di Puskesmas Sumbang 1 - Nanda Kusuma; Madyo Maryoto; Tri Sumarni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Stroke is a manifestation of systemic disease in old age in the form of impaired blood circulation to the brain which causes neurologic deficits. One of the effects that causes non-hemorrhagic stroke is weakness in the limbs of half the body (hemiparesis). This paper aims to determine the application of range of motion (ROM) to muscle strength in non-hemorrhagic stroke patients. The method used in writing this scientific paper is the descriptive method with 1 respondent through interviews, observation, documentation. The results of research from non-hemorrhagic stroke patients who were given range of motion (ROM) training intervention after nursing care for 3x24 hours showed an increase in muscle strength in the right lower extremity. The conclusion is that there was an increase in muscle strength after range of motion (ROM) exercises were carried out on non-hemorrhagic stroke respondents at the Sumbang 1 Community Health Center.